Long-Term Safety and Efficacy of Single or Repeated Intra-Articular Injection of Allogeneic Neonatal Mesenchymal Stromal Cells for Managing Pain and Lameness in Moderate to Severe Canine Osteoarthritis Without Anti-inflammatory Pharmacological Support: Pilot Clinical Study - Cabon, Quentin; Febre, Marine; Gomez, Niels; Cachon, Thibaut; Pillard, Paul; Carozzo, Claude; Saulnier, Nathalie; Robert, Clément; Livet, Véronique; Rakic, Rodolphe; Plantier, Nadia; Saas, Philippe; et al. (Frontiers in Veterinary Science, 2019)
Objective: To explore the long-term safety and efficacy of canine allogeneic mesenchymal stromal cells (MSC) administered intra-articularly as single or repeated injections in appendicular joints of dogs affected by moderate to severe refractory osteoarthritis. Study design: 22 pet dogs were recruited into a non-randomized, open and monocentric study initially administering one cellular injection. A second injection was offered after 6 months to owners if the first injection did not produce expected results. Materials and Methods: Anti-inflammatory treatment (if prescribed) was discontinued at least 15 days before the onset of treatment. Each injection consisted of at least 10 million viable neonatal allogeneic mesenchymal stromal cells obtained from foetal adnexa. Medical data was collected from veterinary clinical evaluations of joints up to 6 months post-injection and owner’s assessment of their dog’s mobility and wellbeing followed for a further two years when possible. Results: Mild, immediate self-limiting inflammatory joint reactions were observed in 5/22 joints after the first injection, and in almost all dogs having a subsequent injection. No other MSC-related adverse medical events were reported, neither during the 6 months follow up visits, nor during the long-term (2-y) safety follow up. Veterinary clinical evaluation showed a significant and durable clinical improvement (up to 6 months) following MSC administration. Eight dogs (11 joints) were reinjected 6 months apart, sustaining clinical benefits up to 1 year. Owner’s global satisfaction reached 75% at 2 years post-treatment Conclusion. Our data suggest that a single or repeated intra-articular administration of neonatal MSC in dogs with moderate to severe OA is a safe procedure and confer clinical benefits over a 24-month period. When humoral response against MSC is investigated by flow cytometry, a positive mild and transient signal was detected in only one dog from the studied cohort, this dog having had a positive clinical outcome.